Silencing ScGUX2 reduces xylan glucuronidation and improves biomass saccharification in sugarcane - Gallinari, Rafael Henrique; Lyczakowski, Jan J.; Llerena, Juan Pablo Portilla; Mayer, Juliana Lischka Sampaio; Rabelo, Sarita Cândida [UNESP]; Menossi Teixeira, Marcelo; Dupree, Paul; Araujo, Pedro (Wiley, 2024)
There is an increasing need for renewable energy sources to replace part of our fossil fuel-based economy and reduce greenhouse gas emission. Sugarcane bagasse is a prominent feedstock to produce cellulosic bioethanol, but strategies are still needed to improve the cost-effective exploitation of this potential energy source. In model plants, it has been shown that GUX genes are involved in cell wall hemicellulose decoration, adding glucuronic acid substitutions on the xylan backbone. Mutation of GUX genes increases enzyme access to cell wall polysaccharides, reducing biomass recalcitrance in Arabidopsis thaliana. Here, we characterized the sugarcane GUX genes and silenced GUX2 in commercial hybrid sugarcane. The transgenic lines had no penalty in development under greenhouse conditions. The sugarcane GUX1 and GUX2 enzymes generated different patterns of xylan glucuronidation, suggesting they may differently influence the molecular interaction of xylan with cellulose and lignin. Studies using biomass without chemical or steam pretreatment showed that the cell wall polysaccharides, particularly xylan, were less recalcitrant in sugarcane with GUX2 silenced than in WT plants. Our findings suggest that manipulation of GUX in sugarcane can reduce the costs of second-generation ethanol production and enhance the contribution of biofuels to lowering the emission of greenhouse gases.
Keywords: biomass; glucuronidation; hemicellulose; saccharification; sugarcane; xylan